GENDER PROFILING AND UN/CHANGED MISOGYNISTIC LAND OWNERSHIP AND PRACTICES IN MBAISE AND AFIKPO SOCIETIES OF EASTERN NIGERIA - Anyanwu, Edith Ada; Eze, Maudline Adaora; Obinna, Nancy Ngozi (EBSU Journal of Social Sciences and Humanities, 2023)
In most African societies, women are considered and treated as second class citizens. Men dictate the norms that allow them to grab land to the exclusion of women. This study investigates land ownership along with several other misogynistic practices in Mbaise and Afikpo societies of Eastern Nigeria, with a view to ascertaining gender profiling and un/changed misogynistic dispositions as the base of the exclusion of Mbaise and Afikpo women from communal land ownership. Observation, oral interviews, focus group discussion and textual materials from library and internet are the data sources used. Qualitative method and descriptive and interpretive techniques are employed. The analysis shows that land ownership practice, like several other misogynistic practices, is gendered against women. These days, unlike erstwhile, women, who could afford land on their own, are allowed to purchase and own land. The unchanged gendered profiling of land ownership is that women are still denied communitarian free land portions, unlike men. The study condemns gender profiling and misogynistic dispositions against women. It submits that the change making the difference between land ownership as well as the like practices then and now implies the new reconstruction of land ownership and other erstwhile gender profiled practices in Mbaise and Afikpo. It calls for a sustained change through cultural reformation, attitudinal change and enactment of legislations outlawing all forms of gender exclusiveness.